Disseminating research results to kids: practical tips from the Neighbourhoods for Active Kids study. (3rd July 2019) - Egli, Victoria; Carroll, Penelope; Donnellan, Niamh; Mackay, Lisa; Anderson, Berit; Smith, Melody
ABSTRACT: Appropriately disseminating results to children are important because it respects the role they played in the research process. Clearly conveying complex messages to children, however, can be challenging and take a substantial amount of time for researchers. This paper reports on the results dissemination processes and accompanying critical reflection, that occurred during Neighbourhoods for Active Kids study – a community-based health research project with 1102 children aged 8–13 years residing in Auckland, Aotearoa/New Zealand. The results dissemination items included: an individual physical activity and food-purchasing behaviour summary, school physical activity and food-purchasing behaviour summary, colouring-in poster, a video, comic, results booklet, school summary report and school data. The results from critical reflection have been developed into five tips for disseminating results to children. The tips are: consult with children and incorporate their feedback throughout; allow space for change and adaptation; meet children where they are at in the digital world and in the physical world; it's OK to ask for help; and be careful of the words you use. Findings can be used to inform results dissemination activities across a range of social science disciplines.